Artificial Intelligence and Learning Situations: Current Perspectives - Gallego Cuiñas, Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2025)
The integration of artificial intelligence (AI) into the educational sphere is driving a profound transformation in the planning and implementation of learning situations within the competency-based framework established by the LOMLOE. This article provides an academic analysis of how AI enables the automation of didactic design, the personalisation of educational processes, and real-time assessment, in line with current legal requirements. Specific practical cases are presented, and future perspectives are discussed, with particular emphasis on the importance of teacher training, ethics, and sustainability in addressing the challenges posed by this new educational era.